LEGAL GROUNDS FOR THE DEVELOPMENT OF THE STATE POLICY IN CHILDREN'S HEALTHCARE PROTECTION IN THE RUSSIAN FEDERATION - Yu.E. Lapin (Вопросы современной педиатрии, 2007)
Scientific center of children's health, Russian academy of medical sciences the presented article is dedicated to the urgent issue — formation of the legal grounds of the state policy in children's healthcare protection. Based on the logical and scicentometric analysis of the main international documents on the children's rights there have been pointed out the key provisions, which should be taken into account during the development of measures for the state regulation of public relations in the interests of the children under modern conditions of the Russian federation.Key words: children's rights, children's healthcare protection, state policy, international documents.